Innovations in Coffee: Patents Reveal in Indonesia - Maidina, Maidina; Ferianto, Ferianto; Hendrix, Tommy (LPPM Universitas Terbuka, 2021)
This paper aims to reveal coffee-related innovations based on the number of registered patents in Indonesia. This paper used a desk study with a literature review and a descriptive analysis method. A literature study to identify existing innovations from registered documents through patent mining, sourced from Indonesian and WIPO patent databases. Findings. The results from the Directorate General of Intellectual Property Rights of Indonesia's patent search, the registered patent on coffee is 202 patents. From the invention technology, the innovations group into coffee processing as beverage (53%), coffee processing equipment (27%), extraction process (5%), and coffee breeding or plantation process (3%), and other (11%). Also, 75% of patent owners are not from Indonesia but dominate Switzerland, America, and other countries.